(untitled) (Veterinary Science, 2023)
The aim of this work is to describe a case of mixed resistance, registering for the first time low antiparasitic efficacy against Cooperia curticei in a sheep flock in the province of Salta. The work was carried out in an establishment in the town of Cerrillos, province of Salta. Four groups of 20 animals each were formed: a control group, a group treated with ivermectin, another treated with albendazole and another treated with levamisole. The efficacy results were 50.5% for ivermectin, 68.7% for albendazole, and 99.2% for levamisole. Regarding the efficacy by gender, it was 42.8%, 64.8% and 97% in Haemonchus contortus, 100%, 79.2% and 99.3% for Trichostrongylus colubriformis and 88.5%, 100 % and 100% for C. curticei for ivermectin, albendazole and levamisole respectively. This finding warns about the AR situation and the wide distribution of the use of various chemical groups under study in the region’s flocks should be considered.